(untitled) (World Economics and Finance Bulletin, 2024)
This article focuses on the prospects of the financial systems approach to development finance to ensure sustainable access to financial services for microentrepreneurs. It discusses three prerequisites for the success of this approach: the continued application of financial liberalisation policies; the delivery of financial services on a commercially viable basis by emulating the successes of informal financial intermediaries in solving the problems normally experienced by the formal financial sector when serving microentrepreneurs; and the continued appropriate support from governments and the donor community.